Enhanced alkali vapor attack resistance of bauxite-SiC refractories for the working lining of cement rotary kilns via incorporation of andalusite. Issue 18 (15th December 2018) - Ren, Bo; Li, Yawei; Nath, Mithun; Wang, Qinghu; Xu, Yibiao
Abstract: Bauxite-SiC refractories as the working lining of cement rotary kiln are subjected to severe alkali attack due to alternative fuel combustion. Herein, the present work aims to enhance their alkali attack resistance via incorporation of different types of andalusite (aggregates and powder). Results show that addition of andalusite reduces penetration of alkali vapor by decreasing their pore size. In particular, the presence of andalusite aggregate traps alkali vapor inside its pore network, retarding the corrosion of refractory matrix. By comparison, the presence of andalusite powder contributes to formation of liquid corrosion products to block the pores, which prevent alkali vapor from further penetration. Incorporation of andalusite into BSRs is straightforward and sought-after, providing an effective approach for high-performance refractory materials with excellent alkali attack resistance.